The influence of fertilizer addition, cutting frequency and herbicide application on soil organisms in grassland - Lemanski, K.; Scheu, S. (Biology and fertility of soils, 2015)
In Europe, grasslands are among the most important agricultural systems which are subject to continuous management intensification, potentially threatening ecosystem services. We analysed the impact of management of permanent grassland, i.e. fertilizer addition (−NPK and +NPK), cutting frequency (one and three cuts per year) and herbicide application targeting either dicotyledons or monocotyledons, on microorganisms and soil animals. Microbial biomass decreased in treatments cut once with fertilizer addition. However, in treatments cut thrice, microbial biomass did not decline with fertilizer addition, suggesting that cutting frequency alleviates the detrimental effect of fertilizer input. Fungal but not bacterial phospholipid fatty acid biomarkers varied with sward composition, indicating fungi more sensitively respond to changes in grassland management and sward composition than bacteria. The abundance of dipterans and beetles increased with fertilizer addition but decreased with sward-cutting frequency. Epigeic earthworms benefited from a reduced proportion of monocotyledons. The results indicate that microbial parameters more sensitively respond to intensification of management practices in grassland than to soil animals, in particular, early after changes of management practices.